O novo ensino médio nos estados do Ceará, Goiás e Paraná: Experiências e desafios - Carolina Esther Kotovicz Rolon (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The new organization of upper secondary level in Brazil introduced by the law number 13.415 of 2017 began to be implemented in 2022. The present paper focused in analyzing the process involving the translation of national directives to local curriculums and their implementation is selected high schools located in the states of Ceará, Goiás and Paraná. The analysis draws on semi-structured interviews carried online between October 2022 and February 2023 with public agents on the state level, high school principals, teachers and students. The main challenges were to train the school staff to teach according to the new directives and to respect student choices of subjects and classes of the flexible part of the curriculum with the resources available at the schools. The balance between the general and the specific teaching is also an important issue that involves preparing students to compete in selective entry exams in tertiary education without exacerbating existing inequalities.
Keywords: I28; I21; 330; education reforms; upper secondary schooling level; education policies; qualitative analysis